2002
DOI: 10.1089/104303402760128595
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated p14ARFGene Transfer Cooperates with Ad5CMV-p53 to Induce Apoptosis in Human Cancer Cells

Abstract: p14(ARF), a product of the INK4A/ARF locus, induces p53 upregulation by neutralizing the effects of MDM2, a transcriptional target of p53 that antagonizes its function. Here we report that adenovirus-mediated p14(ARF) gene transfer leads to the accumulation of ectopically transduced p53 and to apoptosis in human cancer cells. We constructed an adenoviral vector expressing p14(ARF) (Ad-ARF) and examined its synergistic effect with p53-expressing adenovirus (Ad5CMV-p53 or Ad-p53) in human lung and esophageal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Importantly, we lack data on whether these various proteins are coregulated, and how they might interact. Despite our limited insight, numerous investigators have shown that levels of p53 above a certain 'threshold' almost invariably lead to apoptosis or to enhanced drug sensitivity (Blagosklonny and el-Deiry, 1998;Waugh et al, 1999;Boulay et al, 2000;Tango et al, 2002). While this is not conclusive proof that p53 has a central role in mediating drug sensitivity, it suggests at least an ancillary role.…”
Section: Targeting P53mentioning
confidence: 88%
“…Importantly, we lack data on whether these various proteins are coregulated, and how they might interact. Despite our limited insight, numerous investigators have shown that levels of p53 above a certain 'threshold' almost invariably lead to apoptosis or to enhanced drug sensitivity (Blagosklonny and el-Deiry, 1998;Waugh et al, 1999;Boulay et al, 2000;Tango et al, 2002). While this is not conclusive proof that p53 has a central role in mediating drug sensitivity, it suggests at least an ancillary role.…”
Section: Targeting P53mentioning
confidence: 88%
“…Various approaches to restore the pathway include gene transfer of p53 (Edelman et al 2003;Peng 2005), gene transfer of p53 plus ARF (Lu et al 2002;Tango et al 2002;Huang et al 2003), small molecules to restore the function of mutant p53 (Wang et al 2003), small molecule inhibitors of the p53/mdm2 interaction Vassilev et al 2004), antisense oligonucleotide inhibitors of mdm2 expression , and small molecule inhibitors of the ubiquitin ligase activity of mdm2 (Yang et al 2005). Subnuclear compartmentalization of ARF may now provide an additional target for therapies to activate endogenous p53 and optimize other p53-based strategies.…”
Section: Therapeutic Implications Of Arf's Nucleolar Interactionsmentioning
confidence: 99%
“…41 In the past 2 years, more interest has focused on p14 Arf . Several reports have demonstrated that adenoviral delivery of the p14 Arf gene is capable of inducing cell cycle arrest and apoptosis in a wide variety of tumour models [42][43][44][45][46][47] and can sensitize cells to chemotherapy. 48 Initial reports suggested that intact p53 pathways were required for p14 Arf -mediated cytotoxicity [47][48][49] and that cotransfection with wild-type p53 could enhance the p14 Arf effect.…”
Section: Ink4/arf Locus Provides Two Potential Targets For Gene Therapymentioning
confidence: 99%
“…48 Initial reports suggested that intact p53 pathways were required for p14 Arf -mediated cytotoxicity [47][48][49] and that cotransfection with wild-type p53 could enhance the p14 Arf effect. 46 It now appears that p14 Arf is capable of affecting proteins other than p53, such as E2F-1, 50 HIF1a 51 and topoisomerase I. 52 Cluster analysis of gene expression patterns in mouse embryo fibroblasts indicates that p19 ARF induces expression of both p53-dependent and -independent genes, the latter including members of the B-cell translocation family (Btg/Tob) that can inhibit proliferation in cells regardless of p53 status.…”
Section: Ink4/arf Locus Provides Two Potential Targets For Gene Therapymentioning
confidence: 99%